Distoseptispora motuoensis (Distoseptisporaceae), a new freshwater hyphomycetous species from Xizang Autonomous Prefecture, China - Li, Jia-Ning; Xu, Rong-Ju; Xu, Ke; Zhao, Qi; Zhu, Ying-An (Phytotaxa, 2024)
During an investigation of lignicolous freshwater fungi in Xizang Autonomous Prefecture, China, two collections were obtained from submerged wood in freshwater stream. This study reported a novel species within the genus Distoseptispora, namely Distoseptispora motuoensis, based on phylogenetic results from combined sequence data (ITS, LSU and tef1-α) and morphologies. Distoseptispora motuoensis is characterized by conidia with 7–12-distoseptate, sometimes with percurrent proliferation, which forms another conidium from the conidial apex. Phylogenetic analysis revealed that this species forms a distinct clade with strong support (88% ML, 1.00 PP), and it is also morphologically different from the other species of Distoseptispora.